(The effect of grade and particle size of drying nutmeg Oil) - Djumarman -; Ketaren S.; Hary Fransnicko (Balai Besar Industri Agro, 2004)
As raw material of nutmeg oil industry, commercial dry nutmeg seed can be classified into three grades, which are bejo, polong and old nutmeg seed. Research on the effect of grade and particle size of dry nutmeg seed on the yield and quality of the nutmeg oil has been carried out. This research consist of two steps which are pre-research and main research. The pre-research were choosing the optimum distillation time and analysis of nutmeg seed. The main research carried out using distillation time of 10 hours, particle size of 6 mm, 8mm, 10mm, and three grades of nutmeg seed. This research used factorial completed randomized design with two replications. The best treatment of this research were were distillation of bejo nutmeg seed and particle size of 10 mm, with the yield of nutmeg oil is 19,58% (w/w) and physico-chemical properties as follows : specific gravity (25 C) is 0.881, refractive index (20 C) is 1.476, optical rotation is (+) 19.50, solubility in 95 percent alcohol is 1:0.9, evaporation residue was 0.55%, acid value is 0.87, and ester value is 7.45.